The volume of proximal bone projection can determine the osseous contour after immediate implant placement and guided bone regeneration in severe labial bony deficiency - Monica Wang; Kazuyo Kuribayashi Sato; Lo-Lin Tsai; Wei Jen Chang; Yu-Chao Chang; Chih-Yuan Fang (Elsevier, 2022)
Anterior immediate implant placement (IIP) has many biological and esthetic challenges, including inevitable soft and hard tissue loss after extraction. Previous literatures have discussed the facial bone architecture and defective socket classification. However, none of them discussed the depression of the cervical root area which can be seen frequently after IIP in type IIB and U-shaped defective sockets. In our limited experiences, we found that the labial interproximal bone edges of type IIB and U-shaped defect dominated the esthetic result after IIP. With more labial projection of the interproximal bone present, better esthetic result could be expected in the facial aspect. With adequate evaluation of this osseous scalloping before IIP, both patient and clinician could have a comprehensive understanding of the final esthetic result. This article also detailed the process of patient selection, diagnosis, surgical options, and executions required to achieve functional and esthetic success with IIP and provisionalization.